ALIGNING CSR REPORTING IN MINING INDUSTRY: ROLES OF EXTERNAL RELATIONS, INTERNAL AND ENVIRONMENTAL PRACTICES, AND POLICY - Carolina, Yenni; Manullang, Agnes Theresia (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The expansion of the company can raise social concerns and environmental damage. CSR can be a solution to overcome this problem, but the implementation of CSR in Indonesia is still not optimal. This study aims to identify the factors that affect CSR reporting in Indonesia. The four factors analyzed are External Relations, Internal Practices, Environmental Practices, and Environmental Policies. The research was conducted on the mining sector in Indonesia which is directly related to the environment. Variable testing using SEM PLS. The results of the study show that External Relations and Internal Practices do not have a significant relationship with CSR. In contrast, Environmental Policies and Environmental Practices have a significant and positive relationship with CSR.